Sinergi Cabang-Cabang Ilmu Pengetahuan Alam dalam Kompleksitas Fenomena Fotosintesis pada Tumbuhan - Moh. Hayatul Ikhsan; Sigit Prasetyo (Tarbiyatuna Kajian Pendidikan Islam, 2025)
The phenomenon of plant photosynthesis involves various branches of Natural Sciences, including Biology, Physics, Chemistry, and Earth and Space Science. This study aims to understand the interconnection between these disciplines in explaining the photosynthesis process, which not only produces oxygen but also plays a role in stabilizing Earth's temperature and reducing greenhouse gases. This research adopts an interdisciplinary approach by integrating concepts from each relevant field. The results demonstrate that photosynthesis involves not only biological aspects, such as leaf structure and chloroplasts, but also physical and chemical aspects related to the conversion of solar energy into chemical energy. Furthermore, this study explores the relationship between the photosynthesis phenomenon and Earth sciences in maintaining ecosystem balance and addressing global climate change.